The Use of Fuzzy Logic to Assess Sustainability of Oil and Gas Resources (R/P): Technical, Economic and Political Perspectives - AL-Bazali, Talal; Al-Zuhair, Mohammad (International Journal of Energy Economics and Policy, 2022)
This work presents, based on fuzzy logic, an equation that combine the impact of both technical and non-technical factors on sustainability of oil and gas. The classical formula for oil and gas sustainability factor (a = R/P) was fuzzified to include a risk factor (b) that takes into account risks associated with economic health and political stability of oil and gas producing countries. This was made possible through the introduction of risk impact factor (g) and risk impact weight % (w) into the overall risk factor (b). Results showed that economic factors: oil-revenue dependence; public debt; and institutional structure, all impact oil and gas sustainability. The level of economic diversity was found to play a major role on oil and gas sustainability. It was also shown that political stability should not be overlooked as it could indirectly impact oil and gas sustainability. This is especially true for young political regimes due to lack of long-term clear (institutional) vision; proper strategic planning; in-house knowledge and experience; and decision-making flexibility. A hypothetical case study was presented to show how our fuzzified formula works. Results showed that ‘sustainability’ factor () dropped by 45.1% when including economic health and political stability risk factors.